Kinerja Aliansi Stakeholder Perusahaan: Pemetaan, Analisis, dan Prediksi: Studi Kasus Aliansi PT A dan Bank X - Sari, Hasrini (Universitas Prasetiya Mulya, 2008)
In order to create a sustainable competitive advantage, companies nowadays should offer a superior customer value. One way in achieving this is by understanding their stakeholders and building a long-term relationship with them. This paper is intended to map the stakeholders of Company A (a telecommunication company) using the “six-market-model”. Furthermore one form of a long term relationship, i.e. alliance, is thoroughly analyzed and predicted. The alliance of Company A and Bank X is studied as a case in this research. Analysis shows that this kind of relationship, the alliance, has the potential in giving mutual benefit for each party involved. It could also serve as a source to enhance the company’s competitive advantage. This alliance is predicted to be successful in the long term for three reasons: because it is strongly supported by full commitment of senior management; because it has high alliance competences; and because it has idiosyncratic resources.